Relative Genetic Homogeneity within a Phenotypically Diverse group: The Case of Lake Tana Labeobarbus (Cyprinidae) Species Flock, Ethiopia - Beshera, Kebede. A.; Harris, Phillip M.; Michael, Semhar K. (Zootaxa, 2023)
The Lake Tana Labeobarbus species flock represents one of the world’s most famous examples of lacustrine species radiations. Previous studies of this group have resulted in the description of at least 15 species based on their differences in functional morphology and definition of two clades (lacustrine and riverine spawning clades) based on life history traits. A total of 166 fish representing 14 Labeobarbus species were genotyped using 10 lineage-specific hexaploid microsatellite loci. Six of these loci were developed for this study based on DNA sequence contigs derived from a microsatellite-enriched genomic library of Labeobarbus intermedius from Lake Tana; the remaining four loci were obtained from a previous study. The genotypes of the 10 loci were analyzed to examine genetic diversity and population structure within Lake Tana Labeobarbus. Overall mean allelic richness (NA) was 17.6 alleles per locus and observed (Ho) and expected (He) heterozygosities were 0.84 ± 0.14 and 0.73 ± 0.09, respectively, across all Lake Tana Labeobarbus samples examined. Our analyses reveal that there is little genetic differentiation among species (FST = 0.020–0.099; only 10 of 91 species comparisons were significant), but moderate differentiation (FST = 0.11, p < 0.05) between lacustrine and riverine spawning populations. Relative to previous phylogenetic hypotheses, our phenetic analysis employing the R-based Analysis of Phylogenetics and Evolution (APE) program seems to perform marginally better in revealing lineages within Lake Tana Labeobarbus. Herein, our results are compared to a previous microsatellite-based study of the same populations.